On haptic and motor incorporation of tools and other objects - Carijó, Filipe Herkenhoff; de Almeida, Maria Clara; Kastrup, Virgínia (Phenomenology and the cognitive sciences, 2013)
This article presents a conceptual discussion on the phenomenon of incorporation of tools and other objects in the light of Maine de Biran’s philosophy of the relation between the body and the motor will. Drawing on Maine de Biran’s view of the body as that portion of the material world which directly obeys one’s motor will, as well as on his view (supported by studies in contemporary cognitive science) of active touch as the perceptual modality that is sensitive to objects as fields of forces resisting the perceiver’s movements, we discuss the phenomena of motor incorporation and haptic incorporation, as well as the relation between them. Motor incorporation occurs when something is integrated into the motor system, i.e. when practice enables one to animate an object as directly, effortlessly and fluently as one is able to animate one’s own body. The subject then has the experience of acting there , where the object is located, not at the body–object interface. In order to better understand the phenomenon of motor incorporation, we highlight the phenomenological difference between directly and indirectly moving something. Haptic incorporation occurs when something is integrated into the haptic system, i.e. when an object is used as an instrument for the haptic perception of other objects. Finally, we seek to shed light on the phenomenon of transparency, understanding the transparency acquired by the incorporated object as both a relational property and a matter of degrees.